Accidental colchicine poisoning with fatal outcome after ingestion of meadow saffron (Colchicum autumnale L.) - Danilović, Miloš; Isailović, Jelena; Aleksić, Ivan; Džambas, Jelena; Marinković, Nadica (Vojnosanitetski pregled, 2021)
Introduction. Meadow saffron (Colchicum autumnale L.) is a perennial herbaceous plant belonging to the Lily family (Liliacea). It is similar to the edible wild garlic (Allium ursinum L.). Toxic substance in meadow saffron is alkaloid colchicine. Colchicine poisoning is a very dangerous condition which can lead to a fatal outcome. Case report. A 50-years-old male was addmited to the hospital complaining of weakness, abdominal pain, nausea, vomiting and diarrhea without blood. The day before, the patient ate two plants thinking they were wild garlic and seven hours after ingestion he felt first symptoms. During the course of the hospital stay, he had gastroenterocolitis, acute renal faliure, hepatic lesions and cardiorespiratory insufficiency with a fatal outcome. Post-mortem examination revealed: brain oedema, lung oedema and congestion, heart weighing 700 g with ventricular hypertrophy, myocardial fibrosis, liver congestion and steatosis, spleen congestion, pancreatic fibrosis. Organs sections were taken for histopathological analysis. Body fluids and parts of organs were toxicologically analyzed. Histopathological findings were: brain oedema, diffuse perivascular and interstitial myocardial fibrosis, myocardial haemorrhage, lungs congestion and oedema, microvesicular and macrovesicular liver steatosis, centrilobular liver necrosis, lymphocytic inflammatory infiltrate in liver portions, red pulp congestion of the spleen, kidney congestion and interstitial bleeding, coagulation necrosis of the proximal tubules of the kidney. Toxicological analysis showed colchicine in the blood – 0.011 mg/L, urine – 0.051 mg/L, liver with gallbladder – 0.007 mg/kg, kidney – 0.008 mg/kg. Conclusion. Ingestion of meadow saffron can lead to poisoning with a fatal outcome due to the presence of the alkaloid colchicine. Colchicine intoxication should be suspected in patients with gastrointestinal symptoms after consuming wild plants.